CFD investigation of blind-tee effects on flow mixing mechanism in subsea pipelines. Issue 1 (31st December 2022) - Han, Fenghui; Liu, Yuxiang; Ong, Muk Chen; Yin, Guang; Li, Wenhua; Wang, Zhe
Abstract : Blind tees are widely used in subsea pipelines to enhance the mixing conditions of oil and gas products, but their structural design still relies on experience. In this paper, a series of numerical investigations have been carried out on blind-tee pipes in order to develop an in-depth understanding of their mixing mechanism and clarify the effects of blind-tee structures on the pipe flow. Firstly, the three-dimensional flow conditions in a typical blind tee have been simulated under different Reynolds numbers to investigate the mixing mechanism. Two critical Reynolds numbers for the vortex generations in blind tees are determined in the laminar flow regime, and the fitting curves of blind-tee vorticity dissipations are obtained. Then, the geometrical parameters, including the radial size ϕ, axial length (BSL) and position of the blind section, are varied systematically to study their effects on the flow characteristics and mixing conditions. The results indicate that increasing ϕ and BSL in an appropriate range can strengthen the flow circulation and promote the fluid exchange. Finally, an optimal configuration is obtained, which can improve the mixing capacity of blind tee by 53% in terms of the volume average vorticity as compared to the typical structure.